DETERMINAN PERILAKU PEMERIKSAAN PAYUDARA KLINIS (SADANIS) PADA WANITA USIA SUBUR (WUS) DI PUSKESMAS PANDAAN TAHUN 2020 - Aulia Medicarizky (2020)
Breast cancer ranks first as a malignant disease that occur on breast tissue in Indonesia with the highest estimated incidence of 16.7% of the population. The Ministry of Health is developing an early breast cancer detection program using the Clinical Breast Examination (CBE) method. However, only 1.7% of the population in Pasuruan Regency practice CBE. This study aims to determine the determinants of CBE behavior among women of childbearing age in Pandaan Public Health Center. This study use a cross sectional design. The population is women of childbearing age who visited Pandaan Public Health Center with a total sample of 70 respondents. Sampling using nonprobability sampling method with consecutive sampling technique. The variables studied were age, education, knowledge, attitudes, information exposure, family history, and family support. The results showed that knowledge, attitudes, information exposure, and family support were related to CBE behavior. Meanwhile, age, education and family history were not related to CBE behavior. The most influential factor is information exposure with OR = 13.778. Information exposure are very important for respondents, because the information received can make respondents decide to do breast cancer prevention with CBE.